Perverse Incentives? Labor Market Regulation and Performance in the Public Sector. (29th April 2019) - Chong, Alberto; Cozzubo, Angelo
Abstract : We test the link between labor market regulations and job performance in the public sector using a novel outcome variable, namely, the number of days it takes the postal service to return letters sent to nonexistent foreign addresses, a measure that we argue is an excellent proxy for job performance. We find a positive and statistically significant link between these two variables, regardless of the labor regulation measure employed, changes in specification, and even unlikely endogeneity considerations, which suggest that this finding may be causal.